2019
DOI: 10.18488/journal.8.2019.72.62.72
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Services Sector Impact on Economic Growth of Bangladesh: An Econometric Investigation

Abstract: This study attempts to examine the contribution of the service related sector in the economic growth of Bangladesh during the period of 1973-2017. We used the Gross domestic product (GDP) as a measure of economic growth for Bangladesh. Sub-sectors of service-related sector have been used as explanatory variables along with some control variables. In this study, we apply various econometric tools like as Unit Root test, Granger causality test, ARDL Bound test, Error correction model and Cointegration test to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
(21 reference statements)
1
3
0
Order By: Relevance
“…The results are consistent with (Wijaya et al, 2021), (Mahmud & Rashid, 2006), (Haque et al, 2019), and (Yousuf et al, 2019). In the same way, the study found positive relationship exists between gross fixed capital formation and growth.…”
Section: Normality Testsupporting
confidence: 87%
“…The results are consistent with (Wijaya et al, 2021), (Mahmud & Rashid, 2006), (Haque et al, 2019), and (Yousuf et al, 2019). In the same way, the study found positive relationship exists between gross fixed capital formation and growth.…”
Section: Normality Testsupporting
confidence: 87%
“…In recent years, the service sector has seen substantial development in the country's economy. (Rathore et al, 2019;Yousuf et al, 2019). There has been an average rise of 5.55 % during the previous five years (2015)(2016)(2017)(2018) (Nadeem et al, 2019).…”
Section: Alasan Utama Dari Makalah Ini Dibuat Adalah Untuk Memahami D...mentioning
confidence: 99%
“…Moreover, the estimation of the cointegration vector shows that the services sector contributes positively to Pakistan's economic growth. Yousuf et al [34] attempted to examine the contribution of the service sector in the economic growth of Bangladesh during the period of 1973-2017. Estimation results of the ARDL bound approach indicate the service sector and gross domestic product growth are correlated both in the short-run and long run.…”
Section: Brief Empirical Literature Reviewmentioning
confidence: 99%